Grain, Sequence, System: Three Levels of Reception in the Performance of Laptop Music. - Cascone, Kim (Contemporary Music Review, 2003)
In this article, I address several issues of how audiences -- enculturated by pop media -- form expectations while consuming electronic music in a traditional performance setting, and how these expectations undermine the listening experience.